2022
DOI: 10.3389/fnagi.2022.803332
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Impact of Physical Exercise-Induced Increased Resting Cerebral Blood Flow on Cognitive Functions

Abstract: Brain perfusion declines with aging. Physical exercise represents a low-cost accessible form of intervention to increase cerebral blood flow; however, it remains unclear if exercise-induced amelioration of brain perfusion has any impact on cognition. We aimed to provide a state-of-the art review on this subject. A comprehensive search of the PubMed (MEDLINE) database was performed. On the basis of the inclusion and exclusion criteria, 14 studies were included in the analysis. Eleven of the studies conducted we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 112 publications
(148 reference statements)
0
8
0
Order By: Relevance
“…Moreover, that saccade duration and gain did not vary pre-to postexercise indicates that the RT reduction was unrelated to an explicit or implicit strategy designed to reduce planning times to enhance response accuracy (i.e., so-called speed-accuracy trade-off) (Fitts, 1954). Instead, the RT findings support a myriad of studies reporting that a single bout of active exercise elicits a short-term "boost" to executive function (for meta-analyses see Chang et al, 2012;Lambourne & Tomporowski, 2010;Ludyga et al, 2016; see also Renke et al, 2022). As well, the increase in BV during the active exercise condition -and not the non-exercise control condition -suggests that an exercise-mediated increase in CBF may support improved executive function (Kleinloog et al, 2019;Tari et al, 2020; for review of cerebral hypoperfusion and executive function see Poels et al, 2008).…”
Section: The Metabolic Demands Of Active Exercise Increase Cbf and De...mentioning
confidence: 72%
“…Moreover, that saccade duration and gain did not vary pre-to postexercise indicates that the RT reduction was unrelated to an explicit or implicit strategy designed to reduce planning times to enhance response accuracy (i.e., so-called speed-accuracy trade-off) (Fitts, 1954). Instead, the RT findings support a myriad of studies reporting that a single bout of active exercise elicits a short-term "boost" to executive function (for meta-analyses see Chang et al, 2012;Lambourne & Tomporowski, 2010;Ludyga et al, 2016; see also Renke et al, 2022). As well, the increase in BV during the active exercise condition -and not the non-exercise control condition -suggests that an exercise-mediated increase in CBF may support improved executive function (Kleinloog et al, 2019;Tari et al, 2020; for review of cerebral hypoperfusion and executive function see Poels et al, 2008).…”
Section: The Metabolic Demands Of Active Exercise Increase Cbf and De...mentioning
confidence: 72%
“…Physical activity or exercise may improve perfusion in those brain regions (e.g., hippocampus and anterior cingulate) causing structural and functional changes that contribute to the cognitive improvement. 48 , 49 A study reported that moderate exercise could increase the amplitude response of the cerebral artery blood flow velocity, which was associated with improved cardiopulmonary fitness. 50 Our current study showed that the flow velocity of basilar artery was significantly increased in the Baduanjin group compared to the control group, with a significant group and time interaction, which may indicate a positive effect of Baduanjin on cerebral blood flow changes in basilar artery.…”
Section: Discussionmentioning
confidence: 99%
“…Several explanations are possible for the cognitive benefit of PA and muscle strength. First, regular PA correlates with several health benefits, including glucose homeostasis, fatty oxidation, improved cardiovascular function, and an enhanced neuro-immune system, as well as better brain health and a reduced risk of dementia and cognitive impairment [ 16 ]. Second, participating in PA improves the cerebral cortex and increases blood supply to the associated areas of the brain, which aids brain processing speeds [ 16 ] and reduces inflammatory responses associated with the deterioration of brain function [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, regular PA correlates with several health benefits, including glucose homeostasis, fatty oxidation, improved cardiovascular function, and an enhanced neuro-immune system, as well as better brain health and a reduced risk of dementia and cognitive impairment [ 16 ]. Second, participating in PA improves the cerebral cortex and increases blood supply to the associated areas of the brain, which aids brain processing speeds [ 16 ] and reduces inflammatory responses associated with the deterioration of brain function [ 16 ]. Third, regular PA increases hippocampal neurogenesis in conjunction with neurochemicals such as brain-derived neurotrophic factors and insulin-like growth factors [ 17 ], improving neural plasticity and reducing cognitive impairment levels [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation